Controllability of Combustion Process and Fuel Combustion Control System in Diesel Engines - G. M. Kukharonak; E. A. Lazarev (Наука и техника)
The paper considers the problems concerning the control of fuel combustion process in diesel engines. The basic concepts, definitions and evaluations of efficiency of fuel combustion control are given in the paper. Control methods of combustion process have been analyzed. The paper contains the basic points of mathematical model of combustion process. Private criteria of controllability of combustion process and complex criterion that takes into account evaluated property are proposed in the paper. Control methods have been combined in classification groups with the purpose to reduce a search range of an effective control method. The state and prospects concerning development of control systems of combustion process in diesel engines have been analyzed.